Effectiveness of secondary and tertiary prevention for violence against women in low and low-middle income countries: a systematic review - Lucy Kirk; Samantha Terry; Kamalini Lokuge; Jessica L. Watterson (BMC, 2017)
Abstract Background Violence against women (VAW) is a major problem worldwide, with one in three women experiencing violence in their lifetime. While interventions to prevent violence (primary prevention) are extremely important, they can take many years. This review focuses on secondary and tertiary prevention interventions that address the needs of survivors of violence and aim to prevent recurrence. This review also focuses on studies taking place in low and low-middle income countries, where rates of VAW are highest. Methods Searches of peer-reviewed and grey literature took place from March-June 2016 through databases (Embase, CINAHL, WHO Global Index Medicus, Medline, PsychINFO, Web of Science, Cochrane Library, Applied Social Sciences Index and Abstracts and Sociological Abstracts) and by consulting experts in the field. Only primary research was eligible for inclusion and studies had to focus on secondary or tertiary prevention for survivors of VAW in low or low-middle income countries. All study designs were eligible, as long as the study examined client-related outcome measures (e.g., incidence of violence, health outcomes or client satisfaction). Data were extracted and quality of the studies was assessed using the Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies and a qualitative quality assessment tool developed by Mays and Pope. Due to the low number of results and heterogeneity of the study populations and outcomes, a narrative synthesis was conducted and evidence was summarized. Results One thousand two hundred fifteen studies were identified through the search strategy and 22 of these met the eligibility criteria. Overall, the evidence for interventions is weak and study limitations prevent definitive conclusions on what works. There is some evidence that interventions targeting alcohol use, both among perpetrators and survivors, may be effective at reducing VAW through secondary prevention, and that psychotherapy might be effective for survivors of non-partner sexual violence through tertiary prevention. Finally, some evidence exists for crisis centres increasing survivors' access to services (through both secondary and tertiary prevention), however, assessment of their impact on future VAW are needed. Conclusions Though some interventions for survivors of VAW have shown evidence of effectiveness, further research is needed, especially high-quality studies with quantitative outcome data.